Report of the Committee on Road Safety and Traffic Management - Planning Commission (Planning Commission, 2007)
Road safely is a multi-sectoral and multi-dimensional subject. Il includes orderly development and management of roads, provision of safer vehicles, and a comprehensive response to accidents. It relies on modem traffic management systems and practices, improved safety standards in design, construction, operation and maintenance of roads, and production and maintenance of safer vehicles. Owing to unsafe conditions on roads, the rate of accidents in India has been high. According to WHO statistics for 2002, out of about 11.8 lakh road accident deaths across the world, 84,674 deaths were reported from India alone. In the year 2004, the number of road accident deaths in India increased to 92,618.
Planning Commission Government of India
Planning Commission Government of India